Megatrendy w hotelarstwie wyznaczane przez wielkie systemy hotelowe - Jedlińska, Maja (Mega-Trends in Hotel Industry Created by Large Hotel Systems, 2008)
Globalization in economy constitutes the factor stimulating the emergence of global developmental tendencies, so called mega-trends. They also occur in hotel industry and stem from innovative activities of the biggest international hotel systems, the oligopolies at hotel markets. Within 8 biggest systems there are implemented interesting solutions, which are later assimilated by other participants of this market. The study presents the examples of such innovations and takes up an attempt of presenting the list of mega-trends. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 173-180